Association mapping of leaf traits in spinach (Spinacia oleracea L.). Issue 3 (25th April 2016) - Ma, Jianbing; Shi, Ainong; Mou, Beiquan; Evans, Michael; Clark, John R.; Motes, Dennis; Correll, Jim C.; Xiong, Haizheng; Qin, Jun; Chitwood, Jessica; Weng, Yuejin
Abstract: Spinach ( Spinacia oleracea L.) is an important leafy vegetable crop grown worldwide. Leaf traits, surface texture (smooth, savoy or semi‐savoy), petiole colour (different shades of green vs. purple) and edge shape (serrate vs. entire), are important commercial traits of spinach. Association mapping for the three traits was conducted on 323 USDA spinach germplasm accessions, originally collected from 33 countries and representing the entire USDA spinach germplasm collection. The majority of accessions were from Europe (36.3%), Asia (25.3%) and North America (15.8%). The majority of the spinach accessions (82.0%) were smooth (unwrinkled types), whereas the savoy and semi‐savoy types (wrinkled types) accounted for 18.0%. The collection contained 74.9% green petiole types, while the purple petioles consisted of 25.1%. The collection consisted of 27.2% serrated leaf types and 72.8% entire leaf edge types. Genotyping‐by‐sequencing (GBS) was used for single nucleotide polymorphism (SNP) discovery, and SNPs were used as genotypic data to conduct genetic diversity and association mapping of the three leaf traits. Five genetic subpopulations and principal components (PCs) were postulated bystructure 2 and JMP Genomics 7 for this association panel. Five, seven and 14 SNPs were identified to be associated with surface texture, edge shape and petiole colour, respectively. This study provides us an approach to identify SNP markers through association analysis in spinach and thus leads to select these three leaf traits through marker‐assisted selection in spinach breeding programme.